Culture, community, and development - Phillips, Rhonda; Brennan, Mark A. (New York : Routledge, 2020)
"Culture is a living thing. In social settings, it is often used to represent entire ways of life, including rules, values and expected behavior. Varying from nation to nation, neighborhood to neighborhood, and beyond even in the smallest localities, culture is a motivating factor in the creation of social identity and serves as a basis for creating cohesion and solidarity. This book explores the intersection of culture and community as a basis for locally and regionally based development by focusing on three core bodies of literature: theory, research, and practice. The first section, theory, uncovers some of the more relevant historical arguments, as well as more contemporary examinations. Continuing, the research section sheds light on some of the key concepts, variables, and relationships present in the limited study of culture in community development. Finally, the practice section brings together research and theory into applied examples from on the ground efforts. During a time where the interest to retain the uniqueness of local life, traditions, and culture is significantly increasing in community-based development, the authors offer a global exploration of the impacts of culturally based development with comparative analysis in countries such as Korea, Ireland and the United States. A must-read for community development planners, policy makers, students and researchers"--
OCLC-licensed vendor bibliographic record.
Keywords: Community development -- Case studies; Group identity -- Case studies; Culture -- Case studies; ARCHITECTURE / Landscape; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development